Evaluation of the Antioxidant Properties and Cytotoxic Activity of 1,3-dioxolane Derivatives Imidazole - S. S. Zykova; M. V. Shustov; V. S. Talismanov (Разработка и регистрация лекарственных средств, 2023)
Introduction. Modern chemotherapy widely considers the role of antioxidant and pro-oxidant methods in the treatment of oncologic pathologies. The use of agents that cause an increase of ROS is a relevant way to destroy tumors. At the same time, there is evidence of the ability of some antioxidants to lead to the cancer cells apoptosis through the generation of free radical forms of oxygen due to disruption of cellular homeostasis. The combination of the «Ecolum» biosensor using technique, antiradical activity data, and information about the cytotoxicity of compounds used in the study allows us to consistently conduct low-cost screening of as antioxidant, as antiradical activities and potentially reduce the required number of expensive cytotoxicity determinations using tumor cells.Aim. The main target of our work is the evaluation of antioxidant and cytotoxic activities of 1,3-dioxolane derivatives of imidazole using antioxidant, antiradical and cytotoxicity tests in vitro.Materials and methods. To carry out this study, 1,3-dioxolane derivatives of imidazole were obtained. The antiradical tests was performed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Antioxidant properties were assessed within the Ecolum biosensor in the state of oxidative stress. Cytotoxic activity was assessed in GIST-T1 cell culture using the MTT test (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide).Results and discussion. Data from studies of the antioxidant activity of substances using the «Ecolum» biosensor showed varying degrees of damage to the biosensor in the absence of antioxidant action. The antiradical potential, initially used to reveal a possible mechanism of antioxidant action, actually demonstrated a possible mechanism of toxic action of substance 2c due to its antiradical effect comparable to the standard (Trolox), but the substance has the highest cytotoxicity. However, the properties of substance 2a shows that the direct correlation discussed earlier is not found in all cases.Conclusion. The asessment of the antioxidant properties and cytotoxic activity of 1,3-dioxolane derivatives of imidazole demonstrated the relevance of further searching for connections between the results of substances binding with the Ecolum biosensor under conditions of oxidative stress, their antiradical potential and cytotoxic properties. This combination of tests will potentially reduce the cost of screening through the use of an available biosensor, establish a possible mechanism of action aimed at redox balance, and confirm previously obtained data through the use of tumor cell culture.